Leaving the EU Door Ajar for Turkey - Joseph, Joseph S. (Études helléniques / Hellenic Studies, 2004)
This article looks at EU-Turkish relations and the report issued by the European Commission in Ocrober 2004 recommending opening of accession negotiations. The Commission suggests that a three-pillar approach should be followed during the negotiations in order ro guarantee that harmonization with the acquis communautaire and the political reform process are consolidated, broadened and properly implemented by Turkey. lt also points out that accession negotiations are an open-ended process that will be suspended if Turkey breaches basic EU principles like democracy and respect for human rights. The article argues that the case of Turkey is different and more challenging from previous accessions for several reasons. A major issue is whether the internai sociopolitical dynamics and external orientations of Turkey can be compatible with the changing dynamics of the European integration process. It concludes that during the protracted period of accession negotiations Europe and Turkey will find out wherher they can share a common future which will reconcile their different pasts.